Housing Industry Readiness Factors and Indicators to Implement Green Building Development - P. Gomez, Christy; Ting Tiew Yung, Gordon (International Journal of Sustainable Construction Engineering and Technology, 2018)
The importance of having a sustainability agenda has stimulated greater interest for green construction. However, Malaysia is still moving at a slow pace in green building development as compared to other Asia Pacific countries. This paper focuses on investigating the housing industry’s key stakeholders’ readiness factors with regards to the implementation of the green building concept. The first aspect being the relative importance of the design teams’ competencies and commitment in designing green building projects; the second being the factors affecting developer’s decision to procure green buildings; and most importantly and thirdly, the readiness of the housing industry to implement green building development. A questionnaire survey data collection process was undertaken with ‘design consultants and architects’ for the first objective and ‘housing developers’ for the second and third objective. It was found that the most important competencies of the design team in designing green buildings are: knowledge relevant to green design; attention to green design and construction details and offering suggestions to improve green design. The key ‘commitment’ readiness factor identified is the commitment of the architect to produce green design. Whilst the key factors affecting clients’ decisions to procure green buildings are: experience on green buildings; clients’ knowledge on green buildings; commitment of client organizations to provide finance for green buildings; reliability and quality of specifications, and leadership skills and responsibility of constructor. Clearly, the readiness of the housing industry in the development of green buildings is not at a high level, with 41% of the respondents on average acknowledging that the readiness level of their companies is low.